Halal food knowledge among non-muslim food-service workers in General Santos City, Philippines - Ibrahim, Aladin; Pamplona, Pacita Mae; Antonio, Jerald; Carranza, Timothy; Sumagaysay, Kristian (Journal of Halal Product and Research (JHPR), 2023)
This study aims to identify the level of halal knowledge of non-Muslim food service workers in terms of selection of ingredients and cooking procedure. It used descriptive survey method comprising of one hundred purposely selected respondents. The researchers developed a test-type survey questionnaire aimed to identify the level of halal knowledge non-Muslim food service workers. Frequency counts, percentages, and mean were used to analyze the data. Findings showed that workers' knowledge on selection of ingredients is good, and satisfactory on cooking procedures knowledge. The research contribute to the limited researches on halal knowledge in the area.